Accessibility of two urban forms of the inner periphery. Configurational and visibility análisis - Ezquerra, Isabel (2022)
The first outskirts of many European cities, built between the fifties and seventies of the last century, were characterized by the profusion of unitary actions based on the principles of functionalist urbanism –massive housing estates– and other urban forms that resulted from a gradual growth that was more or less planned and closer to the traditional system based on streets and blocks – “ordinary peripheries”–. Faced with more specific approaches that delve into the original enclave character of housing estates, without considering their current urban context, this research aims to demonstrate and morphologically compare the accessibility conditions presented by both types of urban growth. The study is based on an adaptation of the "Node and Place Value" model, developing a multi-scalar configurational and visibility analysis in two estates of the city of Zaragoza and their corresponding “ordinary peripheries”. The results show that the relative situation of the housing estates in the city has changed over time, moving in many cases from a position of isolation on the periphery to a “pericentral position”. Both forms are well integrated into the global urban network. However, at intermediate scale the housing estates show a worse accessibility than the fragments of “ordinary periphery”. On a fragment scale, the latter are also visually safer and more accessible. These analysis can be useful for planning to improve accessibility and revitalize these urban forms.